2015
DOI: 10.1016/j.ejca.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis, stage and oestrogen receptor status of contralateral breast cancer in relation to characteristics of the first tumour, prior endocrine treatment and radiotherapy

Abstract: Prognosis, stage and oestrogen receptor status of contralateral breast cancer in relation to characteristics of the first tumour, prior endocrine treatment and radiotherapy.Alkner, Sara; Ehinger, Anna; Bendahl, Pär-Ola; Rydén, Lisa; Fernö, Mårten Link to publication Citation for published version (APA): Alkner, S., Ehinger, A., Bendahl, P-O., Rydén, L., & Fernö, M. (2015). Prognosis, stage and oestrogen receptor status of contralateral breast cancer in relation to characteristics of the first tumour, prior end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
(31 reference statements)
3
13
0
Order By: Relevance
“…Previous studies by our group showed that characteristics of BC2 have the highest influence on prognosis after development of CBC, although the characteristics of BC1 continue to have some prognostic impact [33]. GPR30 PM + staining in both BC2 and LGL2 was associated with increased risk of BCD (Table 2; Fig 5A and 5B; HR BC2 = 1.7; 95% CI = 1.1-2.7; p = 0.03, and HR LGL2 = 2.0; 95% CI = 1.1-3.4; p = 0.02).…”
Section: Gpr30 Expression and Risk Of Bcd In Cbc Patientsmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies by our group showed that characteristics of BC2 have the highest influence on prognosis after development of CBC, although the characteristics of BC1 continue to have some prognostic impact [33]. GPR30 PM + staining in both BC2 and LGL2 was associated with increased risk of BCD (Table 2; Fig 5A and 5B; HR BC2 = 1.7; 95% CI = 1.1-2.7; p = 0.03, and HR LGL2 = 2.0; 95% CI = 1.1-3.4; p = 0.02).…”
Section: Gpr30 Expression and Risk Of Bcd In Cbc Patientsmentioning
confidence: 82%
“…Patient inclusion and number of CBC successfully stained and scored for GPR30 are summarized in Fig 1. Followup information was retrieved from patient charts, and cause of death and overall survival data were accessed from the Swedish National Board of Health and Welfare in March 2014. Evaluation of ER, PR, Ki67 and HER2 have been previously described [26,27].…”
Section: Patient Cohort and Tma Preparationmentioning
confidence: 99%
“…For example, the CYT method changed during the time periods studied, making results in relation to PR harder to interpret. The cohort represents patients with CBC, and although our previous studies have shown BC2 to be the major determinant of prognosis after the development of CBC , the prognosis after BC2 could still be affected by the first breast cancer. However, as the same cohort was analysed in relation to prognosis for both CYT/IHC, this should not affect our results.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, a TMA of patients with contralateral breast cancer (CBC) was used. Inclusion criteria, data abstraction and TMA construction, as well as prognosis and ER/PR status in relation to both tumours and treatment, have been described previously . The TMA included a total of 1328 tumours from 728 patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation